2020
DOI: 10.4103/jrms.jrms_727_19
|View full text |Cite
|
Sign up to set email alerts
|

Revisional surgery after one anastomosis/mini gastric bypass: A narrative review

Abstract: One anastomosis gastric bypass (OAGB)/mini gastric bypass is now considered to be a safe and efficient method for morbidly obese patients but has complications and adverse events such as other surgical procedures. The present paper outlines the need for and the nature of revisional surgery in the long-term following OAGB in accordance with the preferred reporting items for systematic reviews and meta-analysis guidelines. A literature search was carried out in PubMed. All articles on OAGB for which the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
(179 reference statements)
0
2
0
Order By: Relevance
“…several studies have demonstrated that a limb length of more than 250 cm, particularly created in the case of patients with severe obesity, was associated with a higher risk of malnutrition, whereas a 150-cm length led to minimal nutritional deficiencies (76)(77)(78). However, a shorter biliopancreatic limb, especially if associated with a small gastric pouch of less than 9 cm, has the disadvantage to promote the development of GERD in OAGB (18,79,80).…”
Section: Discussionmentioning
confidence: 99%
“…several studies have demonstrated that a limb length of more than 250 cm, particularly created in the case of patients with severe obesity, was associated with a higher risk of malnutrition, whereas a 150-cm length led to minimal nutritional deficiencies (76)(77)(78). However, a shorter biliopancreatic limb, especially if associated with a small gastric pouch of less than 9 cm, has the disadvantage to promote the development of GERD in OAGB (18,79,80).…”
Section: Discussionmentioning
confidence: 99%
“…In a review study by Kermensaravi et al [ 34 ], it was noted that 4% of patients will require surgical revision of OAGB. In addition, this study also emphasizes the advantages of OAGB when revision or reversal is required owing to its relative simplicity.…”
Section: Discussionmentioning
confidence: 99%